2017
DOI: 10.1159/000464421
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Molecular and Cellular Characterization in Rat Models of Alzheimer's Disease: Neuroprotective Mechanisms of <b><i>Garcinia</i></b> Biflavonoid Complex

Abstract: Background: Recent evidences suggest that cerebellar degeneration may be associated with the development of Alzheimer's disease (AD). However, previous reports were mainly observational, lacking substantial characterization of cellular and molecular cerebellar features during AD progression. Purpose: This study is aimed at characterizing the cerebellum in rat models of AD and assessing the corresponding neuroprotective mechanisms of Garcinia biflavonoid complex (GBc). Methods: Male Wistar rats were grouped and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 56 publications
2
8
0
Order By: Relevance
“…Our findings showed that treatment with Al evidently increases oxidative stress and brain injury as there was significant repression in the levels of SOD, GPx, and CAT in the cerebellar homogenate relative to control. These results corroborated previous findings that Al treatment results to downregulation of antioxidant enzymes, causing an imbalance between pro-oxidant and antioxidant potentials [5,26]. On the contrary, the administration of ESO before and after Al treatment showed a reversal of the deleterious effects on oxidative redox within the cerebellum of rats.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our findings showed that treatment with Al evidently increases oxidative stress and brain injury as there was significant repression in the levels of SOD, GPx, and CAT in the cerebellar homogenate relative to control. These results corroborated previous findings that Al treatment results to downregulation of antioxidant enzymes, causing an imbalance between pro-oxidant and antioxidant potentials [5,26]. On the contrary, the administration of ESO before and after Al treatment showed a reversal of the deleterious effects on oxidative redox within the cerebellum of rats.…”
Section: Discussionsupporting
confidence: 91%
“…The mechanism of cytotoxic and/or neurotoxic substances are thought to be mainly due to the oxidative stress involved in the production of reactive oxygen species (ROS), including superoxide anion, hydrogen peroxide, superoxide radical and hydroxyl radical. Moreover, the degree of oxidative damage is depended on the balance between the oxidative stress and the efficiency of the endogenous antioxidant system that is found in the majority of cells [5]. Generally, brain tissues are highly susceptible to attacks from free radicals due to highly unsaturated lipid contents [28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In line with findings from this study, aluminium has been reported to induce anxiety and memory decline (Crépeaux et al, 2017;Morris et al, 2017;Olajide et al, 2018). The anxiogenic propensity of aluminium can be attributed to the role it plays in mediating neurochemical disturbances and perturbation of neurotransmission in the brain (Caito and Aschner, 2015;Maya et al, 2016;Olajide et al, 2017a;Yokel, 2000). AA and NIC reduced the anxiety levels, as seen in the reduced frequency of stretch attend posture.…”
Section: Discussionsupporting
confidence: 81%